Prevalence of Consanguineous Marriages in UAE Nationals and the Risk of Genetic Diseases (Journal of Medicine, 2023)
Introduction: The occurrence of consanguineous marriages has been common in the Arab populations due to socio-cultural factors. Genetic diseases are rare in the overall population, but their frequency unusually increases as the prevalence of consanguineous marriages increases. The aim of our pilot study was to investigate the extent of consanguinity and its effects on non-communicable genetic diseases, in Emirati population.Methodology: This research was based on a socio-economic survey (SES) conducted by a group of students of Dubai Pharmacy College for Girls in the year 2018. Subjects for this preliminary study were selected by using convenience sampling method from urban regions of United Arab Emirates local households. A questionnaire was designed for this purpose and data was collected during household visits.Results: Our study showed that the incidence of consanguinity is relatively high with a rate of about 65% approximately and 33% of all these consanguineous marriages are of the first cousin and closer marriage type. Our results states that consanguineous marriages have a negative effect on reproductive health factors and in turn posing a risk for occurrence of noncommunicable genetic diseases, congenital malformations, and various chronic and complex multifactorial diseases in Emirati Arab population.Discussion: Genetic counselling and premarital counselling must be accentuated to reduce the risk of genetic syndromes in the population.J MEDICINE 2023; 24(2): 82-88